Motor limitations and growth in children with cerebral palsy - Marques, Joana (2018)
Objectives: to know the weight, length and body mass index of children with cerebral palsy of the district of Lisbon; to analyze the relationship between the commitment and the deficit stature -weight motor. Method: comparative study (children percentile <5 vs percentile >5), composed of a sample of 104 children and their caregivers. Performed the measurement of anthropometric parameters and consultation of the survey data for the Evaluation of the child with Cerebral Palsy. Data analysis performed by SPSS version 20.0. Results: approximately 50% of children presents serious compromise engine. It was found that children with percentile<5 have higher levels of dependence. The significant risk factors were: children with severe limitations the level of gross motor function, orofacial myology polisher, performance in the supply, speech and control of the nanny. Conclusion: approximately 1/3 of the children were in percentile<5 in weight, length and BMI. The children who present greater compromise engine are those that show greater stature-weight deficit.